Positron Emission Tomography Imaging of Tumor Angiogenesis with a (66)Ga-Labeled Monoclonal Antibody - Engle, Jonathan W. (2012)
The goal of this study was to develop a (66)Ga-based positron emission tomography (PET) tracer for non-invasive imaging of CD105 expression during tumor angiogenesis, a hallmark of cancer. (66)Ga was produced using a cyclotron with (nat)Zn or isotopically enriched (66)Zn targets. TRC105, a chimeric anti-CD105 monoclonal antibody, was conjugated to 2-S-(4-isothiocyanatobenzyl)-1, 4, 7-triazacyclononane-1, 4, 7-triacetic acid (p-SCN-Bn-NOTA) and labeled with 66Ga. No difference in CD105 binding affinity or specificity was observed between TRC105 and NOTATRC105 based on flow cytometry analysis. Reactivity of (66)Ga for NOTA, corrected to the end of bombardment, was between 74 and 222 GBq/μmol for both target enrichments with < 2 ppb of cold gallium. (66)Ga-labeling was achieved with > 80% radiochemical yield. Serial PET imaging revealed that the murine breast cancer 4T1 tumor uptake of (66)Ga-NOTA-TRC105 was 5.9 ± 1.6, 8.5 ± 0.6, and 9.0 ± 0.6 %ID/g at 4, 20, and 36 h post-injection, respectively (n = 4). At the last time point, tumor uptake was higher than all organs which gave excellent tumor contrast with a tumor/muscle ratio of 10.1 ± 1.1. Biodistribution data as measured by gamma counting were consistent with the PET findings. Blocking experiment, control studies with (66)Ga-NOTA-cetuximab, as well as ex vivo histology all confirmed the in vivo target specificity of (66)Ga-NOTA-TRC105. Successful PET imaging with high specific activity (66)Ga (> 700 GBq/μmol has been achieved) as the radiolabel opens many new possibilities for future PET research with antibodies or other targeting ligands.